DINAMIKA IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH PADA ASPEK PERANGKAT DAN PROSES PEMBELAJARAN - Ramadhan, Iwan (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
high school level in the independent curriculum. The difference between the curriculum transition was felt by the teacher, starting from the use of teaching tools and the learning process. This is due to the many differences from the 2013 curriculum to the independent curriculum. In addition, the learning process also requires changes such as the previous teaching process in the 2013 curriculum for teachers who are used to it, again requiring adjustments. This research uses descriptive qualitative method. Data were obtained through observation, interviews and documentation techniques which focused on the preparation of teaching tools and the implementation of learning from the 2013 curriculum to an independent curriculum. The results of the research are based on information from the teacher, namely on independent curriculum teaching tools, CP mastery for each teacher followed by the formulation of learning objectives, the flow of learning objectives, designing lessons and assessments. The preparation of the device is not a few teachers who do not fully understand. The tools prepared by the teacher, namely after understanding CP and modules are arranged according to subjects, textbooks, learning videos, as well as learning methods and models that are relevant to students used in the learning process. The results of implementing learning require adaptation by the teacher of curriculum changes. The dominant change in learning is the division of study hours, divided into three hours for intracurricular activities and one hour for co-curricular activities. The implementation of these two things between teachers mutually emphasizes students' soft skills and hard skills which also focuses on students' interests, talents and abilities. Constraints on infrastructure and funding facilities and the ability to compile teaching materials are still experienced by teachers, the solution to overcome these limitations by teachers is to actively participate in training provided by the school to educators as teachers at the school.